Elementary Social Studies Learning Application Based on Tri Kaya Parisudha and Menyama Braya to Improve Elementary School Students' Tolerance - I Wayan Kertih; I Made Tegeh; I Nyoman Tri Esaputra (Jurnal Pedagogi dan Pembelajaran, 2025)
Intolerance among elementary school students remains a challenge that needs to be addressed through contextual learning based on local cultural values. This study aims to develop a social studies learning application based on the values of Tri Kaya Parisudha and Menyama Braya as an effort to improve students' tolerance. The research employed a development model that integrates the initial stages of the simplified Borg & Gall model, namely preliminary study, needs analysis, and initial product design. The subjects of the study included media experts, content experts, language experts, classroom teachers, and fourth-grade elementary school students. Data collection techniques included observation, interviews, and validation questionnaires, while data analysis was conducted using both qualitative descriptive and quantitative methods. Validation results showed a very high level of feasibility for the application, with average validation scores of 94.5% from the language expert, 95% from the content expert, and 96% from the media expert. Practicality tests conducted with students and teachers also indicated average scores above 92%, categorized as highly practical. These findings suggest that the application effectively delivers social studies content in an engaging, communicative, and meaningful way, and is effective in internalizing the values of tolerance in students. This application has the potential to become an innovative, locally-based learning medium that supports character education at the elementary school level.